Skills, majors, and jobs: Does higher education respond? - Johnathan G. Conzelmann; Steven W. Hemelt; Brad Hershbein; Shawn Martin; Andrew Simon (W.E. Upjohn Institute for Employment Research, 2024)
How does postsecondary human capital investment respond to changes in labor market skill demand? We quantify the magnitude and nature of this response in the U.S. 4-year sector. To do so, we develop a new measure of institution-major-specific labor demand, and corresponding shift-share instrument, that combines job ads with alumni locations. We find that postsecondary human capital investments meaningfully respond. We estimate elasticities for degrees and credits centered around 1.3, generally increasing with time horizon. We provide evidence that both student demand and institutional supply-side constraints matter. Our findings illuminate the nature of educational production in higher education.
Keywords: J23; J24; I23; 330; labor demand; skill demand; college major; educational investment